Challenging the Nation-State from within: The Emergence of Transmunicipal Solidarity in the Course of the EU Refugee Controversy - Heimann, Christiane; Mueller, Sandra; Schammann, Hannes; Stürner, Janina (Social Inclusion, 2019)
In the context of the so-called refugee crisis, political disputes about solidarity become a central issue with member states applying competing concepts. At the same time, European cities use transnational networks to implement a new form of solidarity among municipalities via city diplomacy (Acuto, Morissette, & Tsouros, 2017). Analyzing the deadlock between member states and the emerging activities of cities, we scrutinize the limits of existing approaches to political solidarity (e.g., Agustin & Jorgensen, 2019; Knodt, Tews, & Piefer, 2014; Sangiovanni, 2013) to explain this phenomenon. Based on expert interviews and document analysis from a study on transnational municipal networks, we identify an emerging concept of solidarity that challenges the nation states as core providers of solidarity from within: transmunicipal solidarity focuses on joint action of local governments to scale out and scale up.
CRIS-Team WoS Importer:2019-07-16